Conventional Western Treatment Associated With Chinese Herbal Medicine Ameliorates the Incidence of Head and Neck Cancer Among Patients With Esophageal Cancer. (March 2019) - Chang, Chia-Chen; Bi, Kuo-Wei; Lin, Hung-Jen; Su, Yuan-Chih; Wang, Wen-Ling; Lin, Chen-Yuan; Ting, Chun-Fu; Sun, Mao-Feng; Huang, Sheng-Teng
Background: Because of advances in medical treatment, the survival of cancer patients is prolonged. In line with the prolonged survival time of cancer the incidence of second primary cancer has increased. There is currently no effective way to prevent the occurrence of secondary primary cancer (SPC). Objectives: The aim of this study is to evaluate whether Chinese Herbal Medicine (CHM) is correlated with reduced occurrence of second primary cancer (SPC) of head and neck (H&N) in patients with esophageal cancer (EC). Method: We identified 15, 546 patients who were diagnosed with esophageal cancer between Jan 1, 2000, and Dec 31, 2010. The patients with H&N cancer before receiving CHM were excluded. After the selection and matching process, both CHM and non-CHM cohorts each contained 850 individuals. We compared the cumulative incidence of SPC of H&N with or without CHM treatment in patients with EC by the Kaplan-Meier method. NodeXL is used to run a network analysis of CHM to examine the association between herbs and formulas. Results: Compared with non-CHM users, CHM-users showed a reduced incidence rate of SPC of H&N among the patients with EC. Reduced cumulative incidence of SPC of H&N among patients with EC was noted in the CHM cohort compared to the non-CHM cohort. The most commonly used single herbs and formulas were associated with reducing SPC occurrence. Conclusion: We propose that CHM as an adjuvant therapy may prevent the occurrence of SPC of H&N in patients with EC.